Придушення нелiнiйного ефекту оптимiзацiєю властивостей волокон у системах з високою швидкiстю передачi даних з модулятором-дiльником довжин хвиль - Abd, H. J.; Almahanna, M. S. (Publishing house "Academperiodika", 2018)
The nonlinear crosstalk has a detrimental impact on the efficiency of optical communication systems. It becomes stronger with increasing the data transmission rate and transmission distances. We have investigated and estimated the behavior of a nonlinear effect such as the four wave mixing (FWM) under varying the fiber properties such as the frequency channel spacing, fiber cross-section area, and dispersion. In addition, the demeanour of FWM is observed with the use of two types of an advanced modulation format: Return-to-Zero-Frequency Shift Keying (RZ-FSK) and Non Return-to-Zero Frequency Shift Keying (NRZ-FSK). It is found that the FWM power obtained, when the frequency channel spacing is 80 GHz, is drastically reduced to –77dBm in the RZ-FSK scheme, i.e., a reduction ratio in FWM is more than 21%. The simulation also shows that the RZ-FSK modulation format under the channel spacing impact offers a better bit error rate (BER) than NRZ-FSK in modern optical communication systems.